2016
DOI: 10.18632/oncotarget.9944
|View full text |Cite
|
Sign up to set email alerts
|

Hsa-miR-875-5p exerts tumor suppressor function through down-regulation of EGFR in colorectal carcinoma (CRC)

Abstract: Hsa-miRNA-875-5p (miR-875-5p) has recently been discovered to have anticancer efficacy in different organs. However, the role of miR-875-5p on colorectal carcinoma (CRC) is still ambiguous. In this study, we investigated the role of miR-875-5p on the development of CRC. The results indicated that miR-875-5p was significantly down-regulated in primary tumor tissues and very low levels were found in CRC cell lines. Ectopic expression of miR-875-5p in CRC cell lines significantly suppressed cell growth as evidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 47 publications
0
26
0
1
Order By: Relevance
“…To explore whether GACAT1 also functioned as a miRNA sponge, we performed prediction analysis and found that microRNA-875-3p may be a potential target for GACAT1. Previous studies have shown that microRNA-875-3p plays a role as a tumor suppressor gene in a variety of tumors, and its upregulation can often inhibit the proliferation and invasion of tumor cells (18,19). Therefore, we also examined the level of microRNA-875-3p in breast cancer patients, and the results showed that microRNA-875-3p was conspicuously under-expressed in breast cancer.…”
Section: Discussionmentioning
confidence: 94%
“…To explore whether GACAT1 also functioned as a miRNA sponge, we performed prediction analysis and found that microRNA-875-3p may be a potential target for GACAT1. Previous studies have shown that microRNA-875-3p plays a role as a tumor suppressor gene in a variety of tumors, and its upregulation can often inhibit the proliferation and invasion of tumor cells (18,19). Therefore, we also examined the level of microRNA-875-3p in breast cancer patients, and the results showed that microRNA-875-3p was conspicuously under-expressed in breast cancer.…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies have found miR875-5p only in cancer cells, and showed that it promotes cancer cell invasion and epithelial-to-mesenchymal transition [37][38][39] . The present findings revealed expression of miR875-5p in dental mesenchyme, which might be related to the PDGF signaling pathway.…”
Section: Discussionmentioning
confidence: 95%
“…17 More recently, accumulating investigations into miRs and genes have been conducted, which has drawn increasing attention due to their positive involvements in the progression of human CRC 1,18,19 ; however lack of knowledge still persists focusing on distinct delineation for the combination of miR-98 and CLDN1 in CRC. 17 More recently, accumulating investigations into miRs and genes have been conducted, which has drawn increasing attention due to their positive involvements in the progression of human CRC 1,18,19 ; however lack of knowledge still persists focusing on distinct delineation for the combination of miR-98 and CLDN1 in CRC.…”
Section: Discussionmentioning
confidence: 99%